Promoting Freedom, Responsibility, and Learning in the Classroom: The Learning Covenant a Decade Later - Glennon, Frederick E. (Teaching theology and religion, 2008)
This essay discusses an approach to teaching religious studies in a general education or core curriculum that I have experimented with for the last decade, which I call the “Learning Covenant.” The Learning Covenant brings together various pedagogical theories, including transformational, experiential, contract, and cooperative learning, in an attempt to address diverse learning styles, multiple intelligences, and student learning assessment. It has advantages over more traditional teacher-directed approaches to teaching, including meeting student resistance to “required” courses head-on by inviting them to identify learning needs regardless of chosen vocation and meeting them in the context of a religious studies course, recognizing the multiple ways in which students learn and providing a variety of opportunities for students to express their learning, and allowing students opportunity to take increased responsibility for their own learning. The essay will focus on the Learning Covenant's development, components, strengths, and drawbacks.